Expedition down under - Carmi, Rebecca; Speirs, John. (New York : Scholastic, 2001)
Miss Frizzle's class travel to Australia.
"Based on the Magic school bus books written by Joanna Cole and illustrated by Bruce Degan"--T.p. verso.
630
Accelerated Reader AR
Keywords: Australia -- Fiction; Children's stories